Perancangan dan Pembangunan Sistem Pendaftaran Online Pasien Rawat Jalan di RSUD Asembagus Situbondo - Firman Shalihin; Andri Permana Wicaksono; Sustin Farlinda; Mudafiq Riyan Pratama (Politeknik Negeri Jember, 2022)
The outpatient registration process at Asembagus Hospital Situbondo consists of offline and online via the WhatsApp. The problem that often occurs in offline is the accumulation of patients at the registration counter because the number of patients visiting and the number of officers are not comparable, while online often occurs when patient messages register that are buried, which results in patients not being served properly. The impact that can be generated from these things is the perception of patients and families on the quality of hospitals that have not been organized and are not good. The purpose of this study was to design and build an online outpatientThis study used the FAST method with qualitative research and data collection techniques used were observation, interviews and literature study in designing an online outpatient registration system online outpatient.